2014
DOI: 10.1248/bpb.b14-00022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ashwagandha (Roots of <i>Withania somnifera</i>) on Neurodegenerative Diseases

Abstract: Neurodegenerative diseases commonly induce irreversible destruction of central nervous system (CNS) neuronal networks, resulting in permanent functional impairments. Effective medications against neurodegenerative diseases are currently lacking. Ashwagandha (roots of Withania somnifera DUNAL) is used in traditional Indian medicine (Ayurveda) for general debility, consumption, nervous exhaustion, insomnia, and loss of memory. In this review, we summarize various effects and mechanisms of Ashwagandha extracts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 53 publications
(94 reference statements)
1
52
0
Order By: Relevance
“…Adaptogens refer to substances that increase the "state of non-specific resistance to stressors of the everyday life," have normalizing action and are relati used in the Ayurvedic medicinal system to treat general conditions like debility, stress, nervous exhaustion, insomnia, loss of memory, and to enhance cognitive function (Sivarajan and Balachandran, 1994;Warrier et al, 1996;Usmanghani et al, 1997;Kuboyama et al, 2014). Double-blind, placebo-controlled and randomized clinical studies have shown that WS has beneficial precognitive effects on bipolar disorder (Chengappa et al, 2013), and reduction of stress and anxiety measured by the Beck Anxiety Inventory that support its traditional use (Cooley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptogens refer to substances that increase the "state of non-specific resistance to stressors of the everyday life," have normalizing action and are relati used in the Ayurvedic medicinal system to treat general conditions like debility, stress, nervous exhaustion, insomnia, loss of memory, and to enhance cognitive function (Sivarajan and Balachandran, 1994;Warrier et al, 1996;Usmanghani et al, 1997;Kuboyama et al, 2014). Double-blind, placebo-controlled and randomized clinical studies have shown that WS has beneficial precognitive effects on bipolar disorder (Chengappa et al, 2013), and reduction of stress and anxiety measured by the Beck Anxiety Inventory that support its traditional use (Cooley et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Methanolic extract of W. somnifera contains withanolide A, withanoside IV, and withanoside VI. These are reported to induce outgrowths in neurites in neuroblastoma disease (Kuboyama et al, 2014).…”
Section: Antitumor Actionmentioning
confidence: 99%
“…Various Ayurvedic herbs like Amla (Phyllanthus emblica), Guduchi (Tinospora cordifolia), Shankhapushpi (Convolvulus pluricaulis), Ashwagandha (Withania somnifera), Tulsi (Ocimum sanctum), Mandukaparni (Centella asiatica) and Haritaki (Terminalia chebula) have been used in the treatment of memory disorders effectively [105][106][107][108][109][110][111] . Nishteswar et al has reviewed the use of these indigenous herbs in the management of AD and highlighted the potential of these herbs [105] .…”
Section: Role Of Traditional Medicinementioning
confidence: 99%